EFEKTIVITAS MODEL PROJECT BASED LEARNING DENGAN AUGMENTED REALITY TERHADAP PEMAHAMAN DAN KECEMASAN MATEMATIS SISWA SD - Azibah, Arifatul; Ulia, Nuhyal (Elementeris : Jurnal Ilmiah Pendidikan Dasar Islam, 2025)
The use of the Project Based Learning model assisted by Augmented Reality in the field of Education aims to improve conceptual understanding and reduce students' mathematical anxiety on spatial building materials. The research subjects consisted of fifth-grade students at SDN Tlogomulyo, divided into two groups: an experimental class with 28 students and a control class with 29 students. This research is a quantitative experiment. Data collected through test and non-test techniques. The test was conducted with a Post-test at the end of the learning session, while the anxiety questionnaire was given before and after the learning session. The analysis results show that the average Post-test score for concept understanding in the experimental class is 81.7, while in the control class it is only 66.96. The average score for the anxiety questionnaire in the experimental class increased from 60 to 73.5, while the control class only experienced a slight increase from 55.1 to 57.9. Keywords: Augmented Reality (AR), Concept Understanding, Mathematical Anxiety, Project Based Learning (PjBL)